2003
DOI: 10.1159/000070141
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Metastatic Pelvic Lymph Nodes by <sup>18</sup>F-2-Deoxyglucose Positron Emission Tomography in Patients with Prostate-Specific Antigen Relapse after Treatment for Localized Prostate Cancer

Abstract: Aim: To evaluate whether positron emission tomography (PET) with 18F-2-deoxyglucose (FDG) can detect pelvic lymph node metastases in prostate cancer patients who had elevated serum prostate-specific antigen (PSA) levels after treatment. Methods: Twenty-four patients with a rising serum PSA level after treatment for localized prostate cancer were examined with FDG-PET before pelvic lymph node dissection. All patients had negative findings on whole body bone scan and equivocal pelvic computed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 16 publications
0
64
0
1
Order By: Relevance
“…In the study, either local recurrence or systemic metastases were found in 31% of the patients undergoing FDG-PET due to PSA recurrence. In another study on 24 patients with verification of the pelvic lymph nodes, Chang et al (28) found a sensitivity, specificity, positive predictive value and negative predictive value of 75, 100, 100 and 67.7%, respectively. In the study, it was demonstrated that FDG-PET could detect metastatic disease in ~31% of the patients with PSA recurrence following RP.…”
Section: Discussionmentioning
confidence: 96%
“…In the study, either local recurrence or systemic metastases were found in 31% of the patients undergoing FDG-PET due to PSA recurrence. In another study on 24 patients with verification of the pelvic lymph nodes, Chang et al (28) found a sensitivity, specificity, positive predictive value and negative predictive value of 75, 100, 100 and 67.7%, respectively. In the study, it was demonstrated that FDG-PET could detect metastatic disease in ~31% of the patients with PSA recurrence following RP.…”
Section: Discussionmentioning
confidence: 96%
“…It has often been stated that 18 F-FDG PET is not useful in prostate cancer. However, this belief seems to have arisen from some early studies in which 18 F-FDG PET was interrogated in the setting of primary tumor diagnosis or staging of the disease, for which the overall results were unsatisfactory (1)(2)(3).…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…However, this belief seems to have arisen from some early studies in which 18 F-FDG PET was interrogated in the setting of primary tumor diagnosis or staging of the disease, for which the overall results were unsatisfactory (1)(2)(3). The utility of 18 F-FDG PET appears to depend on the phase of the disease; therefore, it may be quite relevant in one phase of the disease but limited in another phase (4,5).…”
Section: Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent reports suggest that Prostascint is not fulfilling its promise and is of little incremental value in selecting patients with local recurrence who may be salvaged by radiotherapy. 50 Chang et al 51 evaluated the role of 18 F-FDG-PET in patients with rising PSA following treatment for localized prostate cancer who had a negative bone scan. Patients underwent lymph-node dissection following PET.…”
Section: Assessment Of Nodal Statusmentioning
confidence: 99%